Skull diploë is rich in aquaporin-4 - Yuji Suzuki; Hiroki Kitaura; Yukimi Nakamura; Akiyoshi Kakita; Vincent J. Huber; Nicholas Capozzoli; Ingrid L. Kwee; Tsutomu Nakada (Heliyon, 2020)
Aquaporin-4 (AQP4) is a water conducting membrane integral protein channel which is widely expressed in the astrocyte system of the brain. During the development of the AQP4 positron emission tomography (PET) imaging agent [11C]TGN-020 (N-(1,3,4-thiadiazol-2-yl)pyridine-3-[11C]-carboxamide), significant radioligand uptake was observed in the skull, where there was no known distribution of any aquaporin family proteins. Herein we confirmed via a newly developed method for bone-tissue immunohistology, a hitherto unrecognized distribution of AQP4, and not AQP1, in the skull. Other bony structures, by contrast, showed virtually no uptake of [11C]TGN-020, and likewise, do not express either AQP4 or AQP1. Immunohistological analysis demonstrated that the AQP4 expression in the skull is restricted to the diploë. Consequently, we suspect AQP4 plays a pivotal role in the formation and maintenance of yellow marrow and the diploë. However, elucidating the exact nature of that role will require further studies.